Typing of Staphylococcus aureus isolated from bovine mastitis cases in Australia and India - Gogoi Tiwari, Jully; Babra Waryah, C.; Sunagar, R.; Veeresh, H.; Nuthanalakshmi, V.; Preethirani, P.; Sharada, R.; Isloor, S.; Bhat, A.; Al-Salami, Hani; Hegde, N.; Mukkur, T. (Blackwell Publishing, 2015)
Objective: To determine the prevalence of the different capsular polysaccharide (CP) and major surface-associated non-CP antigen 336 (SP-336) types among Staphylococcus aureus isolated from bovine mastitis cases in Australia and India. Methods: A total of 414 strains (154 from Australia, 260 from India) isolated from clinical bovine mastitis were included in the study. Mouse antisera raised against CP types (CP1, CP2, CP5, and CP8) or SP-336 were used in slide agglutination tests and compared with detection of cap1, cap5 and cap8 gene fragments by PCR. Results: Serological studies revealed the presence of CP2, CP5, CP8 and SP-336 in 9.1%, 23.4%, 31.8%, and 5.8% of the Australian versus 0.8%, 46.9%, 13.1% and 0% of the Indian isolates, respectively. By PCR, CP1, CP5 and CP8 accounted for 0%, 26.6% and 32.4% of the Australian versus 3.9%, 85% and 8.1% of the Indian isolates, respectively. Conclusions: Both PCR and the serological method demonstrated that CP5 and CP8 are the predominant capsular types in Australia, whereas CP5 is the predominant capsular type in India. The study also demonstrated a strong correlation between both methods of typing for CP1, CP5, CP8 and non-typeable S. aureus strains. High-percentage prevalence of non-typeable isolates in both the countries highlights the importance of continued investigations of the identification of unique surface-associated polysaccharide antigens prevalent among S. aureus isolates for the formulation of CP- and SP-based vaccines for bovine mastitis.